The count of Monte Cristo - Yamamoto, Mitsu; Yamamoto, Mitsu; Dumas, Alexandre, 1802-1870.; Pablo Marcos Studio (New York, N.Y. : Baronet Books, 1992)
Sent to prison on a false accusation in 1815, Edmond Dantes escapes many years later and finds a treasure which he uses to exact his revenge.
"D224-28"--Spine.
Keywords: Revenge -- Fiction; France -- Social life and customs -- 19th century -- Fiction; Adventure stories; Revenge -- Fiction; France -- Social life and customs -- 19th century -- Fiction; Adventure and adventurers -- Fiction; Historical fiction; Adventure stories; Readers